2019
DOI: 10.3390/ma12193080
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Conjugated with Hyperbranched Chlorin e6 Using Disulfide Linkage and Its Nanophotosensitizer for Enhanced Photodynamic Therapy of Cancer Cells

Abstract: The main purpose of this study is to synthesize novel types of nanophotosensitizers that are based on hyperbranched chlorin e6 (Ce6) via disulfide linkages. Moreover, hyperbranched Ce6 was conjugated with hyaluronic acid (HA) for CD44-receptor mediated delivery and redox-sensitive photodynamic therapy (PDT) against cancer cells. Hyperbranched Ce6 was considered to make novel types of macromolecular photosensitizer since most of the previous studies regarding nanophotosensizers are concerned with simple conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 54 publications
(125 reference statements)
0
20
0
Order By: Relevance
“…In fact, some evidence now suggests that CD44 acts as a receptor for proteolytically-modified HA and may be responsible for the modulation of intracellular signaling associated with increased proliferation and invasive capacity [ 17 , 26 , 27 ]. However, because the production of proteolytic enzymes with their cognate targets may be tightly regulated within these tumors, administration of intact, exogenous HA and the delivery of chemotherapeutic agents conjugated with HA has been sufficient in clinical studies to improve patient outcomes and reduce metastatic phenotypes in many cancer types [ 17 , 18 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some evidence now suggests that CD44 acts as a receptor for proteolytically-modified HA and may be responsible for the modulation of intracellular signaling associated with increased proliferation and invasive capacity [ 17 , 26 , 27 ]. However, because the production of proteolytic enzymes with their cognate targets may be tightly regulated within these tumors, administration of intact, exogenous HA and the delivery of chemotherapeutic agents conjugated with HA has been sufficient in clinical studies to improve patient outcomes and reduce metastatic phenotypes in many cancer types [ 17 , 18 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shin Jung et al synthesized a kind of Ce6tetraHA nanocomposite and detected the fluorescence intensity of the drug on mouse CRC cell line HCT116. The drug could be delivered to the tumor site in the way of redox sensitivity and CD44 sensitivity, making the fluorescence intensity of tumor site significantly higher than that of other organs and tissues 130 .…”
Section: Clinical Application Of Ps In Crcmentioning
confidence: 99%
“…The uptake of hyaluronic acid (HA) conjugated nanosystem was proven to be specific to MDA-MB-231 cells and provided an efficient strategy to enhance the photo-cytotoxicity of 5,10,15,20-tetrakis(4-hydroxyphenyl)porphyrin (p-OHTPP) ( Figure 18). Hyaluronic acid was also investigated by Jung et al [190], who synthesized novel types of nanophotosensitizers based on hyperbranched chlorin e6 (Ce6) conjugated with hyaluronic acid (HA) targeting CD44-receptors. The nano-photosensitizers showed higher intracellular accumulation of Ce6 and higher ROS generation and PDT efficacy than free Ce6.…”
Section: Formulation Techniquesmentioning
confidence: 99%
“…The formulations were also selective as confirmed by in vivo tumor xenograft, which demonstrated that the fluorescence intensity in the tumor tissues was much stronger than those in other organs. [189,190].…”
Section: Formulation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation